2014
DOI: 10.1007/s10661-014-4200-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wastes from construction and demolition sector

Abstract: In Republic of Korea, construction and demolition (C&D) waste accounts for 49.9% of the total waste. In the present work, the mineralogical composition, the concentrations of 11 heavy metals, 19 PAH, and 7 polychlorinated biphenyl (PCB) congeners present in the 6 broad category (9 subcategories) of C&D hazardous waste were discussed along with their leaching characteristics. In concrete/mixed cement waste, the concentrations of As, Cr(6+), Hg, and Zn were in the range of 1.76-7.86, ND-1.63, 0.026-0.047, and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The construction waste in most countries is transported to the suburbs for open stacking or traditional landfilling without any treatment [ 6 ]. Thus, waste not only occupies extensive areas of land, but also affects soil and groundwater environments in the vicinity of the construction waste dump [ 7 , 8 , 9 ]. Moreover, during the long-term stacking of construction waste, a large amount of dust is released [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction waste in most countries is transported to the suburbs for open stacking or traditional landfilling without any treatment [ 6 ]. Thus, waste not only occupies extensive areas of land, but also affects soil and groundwater environments in the vicinity of the construction waste dump [ 7 , 8 , 9 ]. Moreover, during the long-term stacking of construction waste, a large amount of dust is released [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Roussat et al [ 16 ] research showed that demolition waste can contain arsenic, fluoride, chromium, cadmium, sulfate, dissolved organic carbon (DOC), and polycyclic aromatic hydrocarbons. Somasundaram et al [ 8 ] detected heavy metals, such as Cr, Hg, and Zn, in concrete and cement waste. They emphasized that the presence of heavy metals in construction waste is largely determined by the source of construction waste.…”
Section: Introductionmentioning
confidence: 99%
“…The leachate generally contains four kinds of pollutants: dissolved organic matter, inorganic large components, heavy metals, and heterogeneous organic compounds [4]. There are lots of heavy metals in the leachate, due to the high heavy metal contents in construction waste [5]. The heavy metals and other harmful substances penetrate into and gradually accumulate within the soil, posing a threat to the ecoenvironment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of C&D waste generation in the European Union was reported about 461 million tons annually (6). In South Korea, C&D waste equals 49.9% of the to-tal generated waste with the production rate of 68 million ton/year (7). The generation rate of C&D waste in the UK estimated about 100 million tons per year (8).…”
Section: Introductionmentioning
confidence: 99%